ANALISIS KAUSALITAS SHOCK HARGA MINYAK DUNIA, PENGELUARAN DAN PENERIMAAN PEMERINTAH DI INDONESIA - Yulfia Mailida; Zul Azhar; Melti Roza Adry (Universitas Negeri Padang, 2019)
This study aims to know and analyze the causality between oil world price, government expenditure and government revenue in Indonesia, which is analyzed using Vector Error Correction Model (VECM) method. The result of this study indicate oil world price and government expenditure have a causality in Indonesia, oil world price do not have a causality government revenue in Indonesia and government expenditurein Indonesia do not have causality government expenditure in Indonesia. Based oo the result of this study it can be conclued that there have two variabel a causality.